Digital authoritarianism: Human rights, geopolitics and commerce - Fredrik Erixon; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2011)
Online censorship is about to take centre stage in the campaign to improve conditions for human rights, cyber security and commercial freedom of exchange on the Internet. Online censorship may be a recent phenomenon, but censorship is not. Yet the extent and impact of censorship has taken new forms, in some instances reached new heights, with the progressive spread of new communication technologies. Censorship and authoritarian control of the Internet has a cascading effect, impinging on national security, external relations with foreign powers, human rights and commerce. (...) The view this paper purports is that foreign actors can help to redress this imbalance by taking China to the WTO for flaunting its commitments. Principally, a WTO case against online censorship could not attack the entire system of censorship in China or any other country. China, and possibly also other countries, is in violation of its WTO commitments when it uses censorship as a tool of discrimination and when its censorship actions are disproportionate to the stated aim of the actions. Hence, the economic rights of other countries get violated by actions to censor the Internet and online communications. (...)
Keywords: 330; Meinungsfreiheit; Internet; WTO-Recht; China